Micro-CT reveals hidden morphology and clarifies the phylogenetic position of Baltic amber water scavenger beetles (Coleoptera: Hydrophilidae). (2nd September 2021) - Arriaga-Varela, Emmanuel; Brunke, Adam; Girón, Jennifer C.; Szawaryn, Karol; Bruthansová, Jana; Fikáček, Martin
ABSTRACT: Water scavenger beetles (Coleoptera: Hydrophilidae) are a broadly distributed group with high extant diversity. However, reliable records from Baltic amber (Eocene) are scarce and limited to two undescribed species previously reported in the literature. Here we study these two specimens plus four additional ones. All specimens were sub-optimal in terms of preservation and visibility of their morphology using traditional light microscopy. Opaque bubbles, cracks in the amber pieces and contracted appendages obscured most of the crucial characters, preventing their formal description and making them prone to misidentification. Here we used X-ray micro-computed tomography (μCT) to reconstruct the morphology of the embedded specimens and described three new species: Anacaena morla sp. nov., Crenitis profechuyi sp. nov. and Helochares fog sp. nov. Micro-CT reconstructions allowed us to visualise the morphology of the specimens to an extent where it was possible to hypothesise possible phylogenetic relations of the new taxa as well as the biogeographic implications of these relationships.